2018
DOI: 10.1097/gox.0000000000001824
|View full text |Cite
|
Sign up to set email alerts
|

Local Cooling as a Step of Treatment for Tissue Ischemia Caused by Hyaluronic Acid Injection-induced Embolism—A Report of 9 Cases

Abstract: Summary:Hyaluronic acid injection is 1 of the most popular procedures in facial rejuvenation and augmentation. It is widely popular in the cosmetic surgery due to several advantages, which include rapid effect, minimal injury, and a short postoperative recovery period. With continuous increase in hyaluronic acid injections, many cases of hyaluronic acid injection-induced embolism have been reported. At present, methods for early treatment of hyaluronic acid injection–induced embolism include local injection of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…The literature and photographic searches yielded 243 individual photographic cases with a total of 738 photographs available for review and scoring using the FOEM system. Information relating to patient demographics was available in 199 cases, filler material and injection site in 195 cases, and symptoms in 149 cases from 120 publications 23–143 from which data extraction was performed and are listed in Table 2. The patient population was predominantly female (88%), with an average age of 38.2 years.…”
Section: Resultsmentioning
confidence: 99%
“…The literature and photographic searches yielded 243 individual photographic cases with a total of 738 photographs available for review and scoring using the FOEM system. Information relating to patient demographics was available in 199 cases, filler material and injection site in 195 cases, and symptoms in 149 cases from 120 publications 23–143 from which data extraction was performed and are listed in Table 2. The patient population was predominantly female (88%), with an average age of 38.2 years.…”
Section: Resultsmentioning
confidence: 99%
“…Although early warm massage may promote vasodilation, local heating will also increase the metabolic rate of tissue, thus reducing the ischemic tolerance of tissue 22 . Therefore, some clinical studies have adopted the method of warm massage during the first 30 min after hyaluronidase injection (the specific temperature is unknown), followed by local cooling with a gauze pad soaked with antibiotic saline solution 22 . Hypothermia slowed the blood flow and increased the resistance of the microvasculature; however, it did not affect the blood reserve capacity and vascular endothelial function 27 .…”
Section: Discussionmentioning
confidence: 99%
“…However, no animal experiments have confirmed that a warm compress is www.nature.com/scientificreports/ conducive to the recovery of vascular embolism. Although not recommended, a cold compress can reduce the local tissue metabolic rate and increase the tolerance to ischemia, which can help treat injection embolization 22 . Therefore, we performed this study to explore the therapeutic effects of the application of a warm compress and a cold compress on filler-induced vascular embolism.…”
Section: Discussionmentioning
confidence: 99%
“…The most serious consequence is the possibility of vascular embolism. This usually occurs when HA is injected into a blood vessel, resulting in the formation of a thrombus or embolism and interruption of the normal blood supply to the vessel, with subsequent development of ulceration or necrosis at the injection site [ [15] , [16] , [17] ]. If the filler is injected into an artery and causes a reversal of blood flow near the bifurcation of the central retinal artery, the filler will advance with the blood flow and eventually form a blockage, resulting in loss of vision [ [18] , [19] , [20] ].…”
Section: Introductionmentioning
confidence: 99%